'Nothing really responsible goes on here': scientists' experience and practice of responsibility. Issue 3 (2nd September 2017) - Glerup, Cecilie; Davies, Sarah R.; Horst, Maja
ABSTRACT: Scientists face increasing demands to integrate practices of 'responsibility' into their working lives. In this paper, we explore these developments by discussing findings from a research project that investigated how publically funded scientists perceived and practiced responsibility. We show that, though the scientists in this study mostly viewed policy discourses such as Responsible Research and Innovation (RRI) as irrelevant to them, they articulated and practiced a range of 'bottom-up' responsibilities, including for producing sound science, taking care of employees, creating 'impact' and carrying out publically legitimate science. The practice of these responsibilities was often shaped by wider dynamics in the governance of knowledge production, such as academic capitalism and the marketisation of universities. Based on these findings, we suggest that RRI scholarship should, first, work to develop a shared language of responsibility with scientists, and, second, more actively address the political context of contemporary scientific research.